2019
DOI: 10.1016/j.jval.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of New Medical Technologies: The Case of Customized Individually Made Knee Implants

Abstract: Objectives: To investigate the impact of insurance coverage on the adoption of customized individually made (CIM) knee implants and to compare patient outcomes and cost effectiveness of off-the-shelf and CIM implants. Methods: A system dynamics simulation model was developed to study adoption dynamics of CIM and meet the research objectives. The model reproduced the historical data on primary and revision knee replacement implants obtained from the literature and the Nationwide Inpatient Sample. Then the dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 58 publications
0
19
0
3
Order By: Relevance
“…With rising healthcare costs worldwide and an increase in patients requiring TKA, there is concern that providing patients with PSI will result in higher costs compared to OTS implants. PSI indeed have higher upfront costs due to the required preoperative imaging and the customised manufacturing process [ 53 ]. However, Culler et al [ 18 ] saw no difference in overall costs, and O’Conner et al [ 21 ] even found significantly lower costs in the PSI group when looking at total postoperative costs up to one year after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With rising healthcare costs worldwide and an increase in patients requiring TKA, there is concern that providing patients with PSI will result in higher costs compared to OTS implants. PSI indeed have higher upfront costs due to the required preoperative imaging and the customised manufacturing process [ 53 ]. However, Culler et al [ 18 ] saw no difference in overall costs, and O’Conner et al [ 21 ] even found significantly lower costs in the PSI group when looking at total postoperative costs up to one year after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There is now over a decade of experience with customized implants, including over 100,000 implantations worldwide. Previous peer-reviewed studies confirm that patient specific TKA implants provide improved fit and alignment 9,10,11,12 , better kinematic function 13,14 , reduced short-term complication rates 15,16 , higher patient satisfaction 17,18 , and overall cost savings 15,16,19,20 when compared to standard off the shelf implants. Data from the UK National Joint Registry (UKNJR), recently released by Beyond Compliance, highlight a lower cumulative revision rate for the custom cruciate retaining implants than that of all other knee implants in the UKNJR 21 .…”
Section: Custom Implants and Toolsmentioning
confidence: 93%
“…Осевая нагрузка на оперированную конечность возможна уже в раннем послеоперационном периоде [1]. Однако на сегодняшний день отсутствуют отдаленные результаты использования подобных металлоконструкций [18,28]. К недостаткам двойных конусов можно отнести малую площадь контакта с нативной костью и высокую стоимость [29].…”
Section: рис 1 рентгенограммы коленного сустава в прямой и боковой проекциях с установленным связанным имплантатом при поступлении в клинunclassified